5a³ - 4ab + 2a³ = (5+2)a³ - 4ab = 7a³ - 4ab.
(-a-7b+5)4ab
a^2b^2(4ab) = 8a^3b^3.
(4ab^2 + 3cd)(4ab^2 - 3cd)
a²-a = a(a-1)
2a(2b-c) :P
To factorize the expression 4ab - 6ab, you first need to identify the common factor between the two terms, which is 2ab. You can then factor out this common factor to rewrite the expression as 2ab(2 - 3). Therefore, the fully factorized form of 4ab - 6ab is 2ab(2 - 3) or simply -2ab.
5a³ - 4ab + 2a³ = (5+2)a³ - 4ab = 7a³ - 4ab.
2a*2b = 4ab
Urmm 4ab ?
(-a-7b+5)4ab
4ab * 3a = 12a2b -----------
a^2b^2(4ab) = 8a^3b^3.
(4ab^2 + 3cd)(4ab^2 - 3cd)
Oh, dude, the product of 4A and b is simply 4Ab. It's like when you mix 4 of something with another thing called b, you get 4Ab. It's not rocket science, just some good ol' multiplication.
4a2 + 4ab - y2 + b2 You cannot simplify this expression because it does not contain like terms, but you can factor it such as: 4a2 + 4ab - y2 + b2 = (4a2 + 4ab + b2) - y2 = (2a + b)2 - y2 = [(2a + b) - y][(2a + b) + y]
ab